Fenomena Phubbing: Suatu Degradasi Relasi Sosial sebagai Dampak Media Sosial - Rafinita Aditia (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—This study aims to find out about the phubbing phenomenon as a degradation of social relations as a result of social media. The term phubbing is an abbreviation of the words phone and snubbing, which are used to show the attitude of hurting the other person by using an excessive smartphone. This type of research used a qualitative approach with descriptive methods. The data needed in this study are qualitative data as primary data in the form of images, words and not numbers in a discourse regarding the phubbing phenomenon as a degradation of social relations as a result of social media. Based on the results of the research, it is found that phubbing behavior can threaten the disruption of ongoing communication relationships, causing social degradation. The social degradation that occurs is due to the impact of phubbing perpetrators' indifference to their environment because they are too busy using smartphones, especially in the use of social media. Therefore it is necessary to limit and control the use of social media properly so that the phubbing phenomenon can be resolved immediately and the degradation of social relations does not occur. Keywords: phubbing, degradation, social relation, social media Abstrak—Penelitian ini bertujuan untuk mengetahui tentang tentang fenomena phubbing sebagai suatu degradasi relasi sosial sebagai dampak dari media sosial. Jenis penelitian yang digunakan menggunakan pendekatan kualitatif dengan metode deskriptif. Data yang dibutuhkan dalam penelitian ini merupakan data kualitatif sebagai data primer berupa gambar, kata-kata dan bukan angka-angka dalam sebuah wacana mengenai fenomena phubbing sebagai suatu degradasi relasi sosial sebagai dampak dari media sosial. Berdasarkan hasil penelitian diperoleh hasil bahwa perilaku phubbing mampu mengancam terganggunya hubungan komunikasi yang sedang berlangsung, sehingga menyebabkan degradasi sosial. Degradasi sosial yang terjadi ialah karena dampak dari keacuhan pelaku phubbing terhadap lingkungannya karena terlalu sibuk menggunakan smartphone, terlebih dalam penggunaan media sosial. Oleh karena itu penggunaan media sosial perlu dibatasi dan dikontrol dengan baik agar fenomena phubbing dapat segera teratasi dan degradasi relasi sosial tidak terjadi. Kata kunci : phubbing, degradasi, hubungan sosial, sosial media